2016
DOI: 10.1186/s13045-016-0357-z
|View full text |Cite
|
Sign up to set email alerts
|

Co-infusion of haplo-identical CD19-chimeric antigen receptor T cells and stem cells achieved full donor engraftment in refractory acute lymphoblastic leukemia

Abstract: BackgroundElderly patients with relapsed and refractory acute lymphoblastic leukemia (ALL) have poor prognosis. Autologous CD19 chimeric antigen receptor-modified T (CAR-T) cells have potentials to cure patients with B cell ALL; however, safety and efficacy of allogeneic CD19 CAR-T cells are still undetermined.Case presentationWe treated a 71-year-old female with relapsed and refractory ALL who received co-infusion of haplo-identical donor-derived CD19-directed CAR-T cells and mobilized peripheral blood stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 14 publications
2
53
0
1
Order By: Relevance
“…The mechanism of this process could be that the G-PBSCs might support the survival of the donorderived CAR-T cells. 11,22 In the present study, we persistently detected donor CAR-T cells in the host peripheral blood after the first infusion of CAR-T cells at a peak level on day 7. Although the CAR-T cells gradually decreased, the CAR-T cells could still be detected until day 40 after infusion.…”
Section: Discussionsupporting
confidence: 52%
“…The mechanism of this process could be that the G-PBSCs might support the survival of the donorderived CAR-T cells. 11,22 In the present study, we persistently detected donor CAR-T cells in the host peripheral blood after the first infusion of CAR-T cells at a peak level on day 7. Although the CAR-T cells gradually decreased, the CAR-T cells could still be detected until day 40 after infusion.…”
Section: Discussionsupporting
confidence: 52%
“…The outcome is also poor for a patient with a higher burden of disease [34]. In addition, it is very difficult to collect sufficient T cells for the construction of CAR-T cells from patients who have an extremely high leukemia burden [23,35].…”
Section: Car-t Cells As Conditioning Regimenmentioning
confidence: 99%
“…Therefore, the donor-CAR-T cells may be safe and effective in allo-HSCT. Recently, Ai et al reported an older patient with refractory ALL, who was treated with low numbers of donor-derived CD19-CAR-T cells and with low dose of recombinant human granulocyte colony-stimulating factor-mobilized peripheral blood stem cells [35]. This patient developed serious GVHD and by treating with anti-GVHD drugs, the related complication was controlled.…”
Section: Car-t Cells As Conditioning Regimenmentioning
confidence: 99%
“…Novel approaches comprise complex combinations as well as sequences of defined cellular products. A case report of a patient with relapsed and refractory B-cell ALL described a combined treatment composed of re-induction chemotherapy, haploidentical co-infusion of CD19-CAR T cells, and mobilized peripheral blood stem cells followed by MSC infusion [91], giving a first example of a highly complex composition of cellular therapy. However, large clinical trials comparing such treatment modalities are often missing and are highly challenging due to the complexity of the therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%